Pengaruh Myofacial Trigger Point Dry Needling dan Neuromuscular Taping terhadap Penurunan Nyeri pada Myofacial Trigger Point Syndrome Otot Upper Trapezius - Rahayu, Putri; , Umi Budi Rahayu, S.Fis, M.Kes (2017)
Background: Myofascial trigger point syndrome is one kind of neck pain disorder that often have felt by the officer. One cause of it is trigger point in musclebelly of the neck muscle especially Upper Trapezius.trigger point is a spot that collect of fibrous and that cause contractur on muscle fiber. There are many kind of physical therapy modalities to get rid of the trigger point and decrease pain in the neck muscle. Two of them are myofascial trigger point dry needling (MTDN) dan neuromuscular taping (NMT). Purpose: To know the effect of MTDN for decrease pain in MTPs of Upper Trapezius muscle (1), To know the effect of NMT for decrease pain in MTPs of Upper Trapezius muscle (2), and To know the different effect of MTDN and NMT for decrease pain in MTPs of Upper Trapezius muscle (3). Methods: Types of this research is quasi experiment. Research design is Two Group Pretest and Posttest for compare MTDN and NMT for decrease pain in MTPs of Upper Trapezius muscle. The method to take the sample use purposive sampling method. This experiment were followed of 16 respondent that consist of 8 respondent in MTDN program and 8 respondent in NMT. The experiment held done in ASYA Physiotherapy and Baby Spa, in Mojokerto, East Java. Result: From result of wilcoxon test which obtained from total WNPDI score, there is significant change with score p = 0,012 on both of two groups. But from result of mann whitney test, there is no significant differences between average pre test and post test with p score is 0,958 and that p>0,05. Conclusions: There is effect of MTDN and NMT for decrease pain in MTPs of Upper Trapezius muscle but There is no different effect of MTDN and NMT for decrease pain in MTPs of Upper Trapezius muscle.